2001
DOI: 10.1021/ic0013025
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Re withN,N‘-Bis(2-pyridylmethyl)ethylenediamine (H2pmen):  Hydrolysis, Dehydrogenation, and Ternary Complexes

Abstract: A number of Re complexes with N,N'-bis(2-pyridylmethyl)ethylenediamine (H2pmen) have been made from [NH4][ReO4]. [ReOCl2(H2pmen)]Cl, [ReOCl(Hpmen)][ReO4], and [ReO2(H2pmen)][ReO4] are related by hydrolysis/HCl substitution. [ReOCl(Hpmen)][ReO4] was structurally characterized and found to contain a water-stable amido-Re bond. Dehydrogenation of the N-donor ligand from each amine to imine with concomitant two-electron reduction of the Re center occurs readily in these systems. With suitable 3-hydroxy-4-pyrones, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…The ReϪN(1) bond lengths in 3a and 4 are similar to the ReϪamido bond lengths recently reported for cationic (oxo)Re V complexes with an acyclic tetradentate Ndonor ligand. [16] As expected, these ReϪN(1) bonds are considerably shorter than the three ReϪN(amine) bonds, which span from 2.110 (6) [16,17] . The lengthening of the ReϪX (X ϭ Cl, I) bonds can probably be accounted for by the presence of intramolecular hydrogen bonds involving the halo ligands and the equatorial NϪH hydrogen atoms [Cl···N(3) 2.968 Å in 3a; I···N(3) 3.262 Å in 4].…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The ReϪN(1) bond lengths in 3a and 4 are similar to the ReϪamido bond lengths recently reported for cationic (oxo)Re V complexes with an acyclic tetradentate Ndonor ligand. [16] As expected, these ReϪN(1) bonds are considerably shorter than the three ReϪN(amine) bonds, which span from 2.110 (6) [16,17] . The lengthening of the ReϪX (X ϭ Cl, I) bonds can probably be accounted for by the presence of intramolecular hydrogen bonds involving the halo ligands and the equatorial NϪH hydrogen atoms [Cl···N(3) 2.968 Å in 3a; I···N(3) 3.262 Å in 4].…”
Section: Resultssupporting
confidence: 62%
“…While there is an extensive literature [16] on mono(oxo)Re V complexes, namely with chelating N-donor ligands, complexes with the cis-[ ReO 2 ] ϩ core are scarce. To the best of our knowledge, the latter class of compounds is comprised of only the five-coordinate cis-[ReO 2 I(PPh 3 ) 2 ] (2) [17] and the six-coordinate cis-[ReO 2 (bipy)(py) 2 ] (bipy ϭ 2,2Ј-bipyridine) [18] and cis-[ReO 2 (OH 2 )(Me 3 tacn)] ϩ (Me 3 -tacn ϭ 1,4,7-trimethyl-1,4,7-triazacyclononane) [11] .…”
Section: Resultsmentioning
confidence: 99%
“…2 Recently we (see reviews 3 ) and others 4 found explicit evidence that platinum group metals, [5][6][7][8][9] rhenium, 10 gold, 11a,b or silver 11c centers provide enormous stabilization of the potentially unstable imines RR′CdNH, and these ligands can be "stored" without changes in the coordinated form under normal conditions for a prolonged time. Moreover, it appears that the formation of imines is one of the major driving forces for some reactions, e.g., condensation of complexed ammonia with ketones, 11 reductions of oximes, 12 oxidative dehydration of amines (e.g., at Fe, 13 Ru, 14,15 Os, 16 Re, 17 and Pt 18 centers), and nucleophilic additions to metal-bound nitriles. 3,4 We expected that the combination of the inertness of coordinated imines RR′CdNH with their high reactivity in the free state could have some intrinsic practical, albeit not yet explored, implications.…”
Section: Introductionmentioning
confidence: 99%
“…In this report the concept of ligand permutation has been extended to '4+1' complexes by using a dianionic, tetradentate N 2 O 2 -donor chelate around the oxorhenium(V) core. Several rhenium(V) complexes with tetradentate ligands have been described, with most of these ligands being of the Schiff base type [7][8][9]. However, we have synthesized the oxorhenium(V) complex [ReOCl(had)] by the reaction of the rhenium(III) starting material [ReCl 3 (MeCN)(PPh 3 ) 2 ] with the tetradentate N 2 O 2 -donor ligand N,N-bis(2-hydroxybenzyl)-2-(2-aminoethyl)dimethyl-amine (H 2 had) in the presence of oxygen with a relatively short reaction time of 30 min.…”
Section: Introductionmentioning
confidence: 99%